If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -1y = -13 Solving -3x + -1y = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. -3x + -1y + y = -13 + y Combine like terms: -1y + y = 0 -3x + 0 = -13 + y -3x = -13 + y Divide each side by '-3'. x = 4.333333333 + -0.3333333333y Simplifying x = 4.333333333 + -0.3333333333y
| e^4=16 | | e^4=6 | | Los(x+25)=3 | | 21x+115=-3x^3+12x^2+17 | | (2x-5)=-3 | | 9/16-33/4 | | 16r+15=-r^2 | | 9y-30=60 | | 3k^2-27k+10=0 | | 5n+119=14n-7 | | 12*x+48=51*x-117 | | X=16a+1 | | 77077= | | 2y=y+11 | | (2x-4)/x=2 | | Ln(x^2-1)=1 | | X+.09x=11 | | 3(2-3x)-4=-(4x-5)+2 | | 62x+110=668 | | 62x+110=168 | | 5/6/1/7 | | Y-3=0(x-4) | | 2x+3=4(2+1) | | content://media/external/file/31459 | | 3x+7=12x+6 | | 9x-11=x+10 | | 16+9x-1-5x=-15+10x | | 16+9x-1-5x=15+10x | | 8a-4(-5a-7)=14a | | x=m | | 33-5v=2v+5 | | (a-10)+(a+10)=0a |